Formação de pedagogos que lecionam Ciências nos anos iniciais do Ensino Fundamental - Souza, Paulo Roberto Lima De (2020)
Science Teaching in the Early Years of Elementary School has been the target of several studies in classroom contexts where both the teaching-learning process of the students and the training of the pedagogue as a teacher who teaches sciences are considered at this level of education. This study aims to gather the results of a theoretical and experiential investigation which aimed to investigate the understanding of the teachers with sciences of nature training from the Instituto de Educação Superior Presidente Kennedy/RN (IFESP)on the organization of the curriculum in this institution to teach sciences. Therefore, a qualitative approach research was done and as data collection instruments it was conducted a Focal Group study and the application of semi-structured questionnaires. Also, a bibliographic study was conducted which discusses the theme in question through a survey based on the categories of analysis according to Bardin (2011) and a documental analysis with a view to investigating the curriculum of the Pedagogy courses in the Federal Universities of Brazil focusing on the disciplines related to Science Teaching. The Brazilian educational legislation in force was considered, as well as studies developed by authors who discuss the initial and continuous training of teachers who teach sciences, such as DemétrioDelizoicov, Marta Maria Castanho Pernambuco, Ana Maria Pessoa de Carvalho and Leonir Lorenzetti. As results we identified that the discussions brought by these authors signal to the need for a curricular change in the pedagogy courses, especially in the disciplines which form pedagogues to teach science in the early years of the Elementary School. The data collected from the group of teachers through questionnaires and application of the Focus Group give body to a suggestion of two programs of the disciplines Theoretical and Methodological Foundations of Science Teaching I and II for the Pedagogy Course of IFESP